Do girls have a nutritional disadvantage compared with boys? Statistical models of breastfeeding and food consumption inequalities among Indian siblings. - Jasmine Fledderjohann; Sutapa Agrawal; Sukumar Vellakkal; Sukumar Vellakkal; Sanjay Basu; Oona Campbell; Pat Doyle; Shah Ebrahim; David Stuckler (PLoS ONE)
Background India is the only nation where girls have greater risks of under-5 mortality than boys. We test whether female disadvantage in breastfeeding and food allocation accounts for gender disparities in mortality. Methods and findings Secondary, publicly available anonymized and de-identified data were used; no ethics committee review was required. Multivariate regression and Cox models were performed using Round 3 of India's National Family and Health Survey (2005-2006; response rate = 93.5%). Models were disaggregated by birth order and sibling gender, and adjusted for maternal age, education, and fixed effects, urban residence, household deprivation, and other sociodemographics. Mothers' reported practices of WHO/UNICEF recommendations for breastfeeding initiation, exclusivity, and total duration (ages 0-59 months), children's consumption of 24 food items (6-59 months), and child survival (0-59 months) were examined for first- and secondborns (n = 20,395). Girls were breastfed on average for 0.45 months less than boys (95% CI: = 0.15 months to 0.75 months, p = 0.004). There were no gender differences in breastfeeding initiation (OR = 1.04, 95% CI: 0.97 to 1.12) or exclusivity (OR = 1.06, 95% CI: 0.99 to 1.14). Differences in breastfeeding cessation emerged between 12 and 36 months in secondborn females. Compared with boys, girls had lower consumption of fresh milk by 14% (95% CI: 79% to 94%, p = 0.001) and breast milk by 21% (95% CI: 70% to 90%, p<0.000). Each additional month of breastfeeding was associated with a 24% lower risk of mortality (OR = 0.76, 95% CI: 0.73 to 0.79, p<0.000). Girls' shorter breastfeeding duration accounted for an 11% increased probability of dying before age 5, accounting for about 50% of their survival disadvantage compared with other low-income countries. Conclusions Indian girls are breastfed for shorter periods than boys and consume less milk. Future research should investigate the role of additional factors driving India's female survival disadvantage.